2016
DOI: 10.4067/s0718-07642016000500005
|View full text |Cite
|
Sign up to set email alerts
|

Extracción con CO2 Supercrítico de Aceite de Semillas de Guanábana (Annona muricata): Cinética, Perfil de Ácidos Grasos y Esteroles

Abstract: Se estudió la extracción de aceite de semillas de guanábana utilizando dióxido de carbono supercrítico a presiones entre 20 y 35 MPa y temperaturas entre 313 y 333 K, con un flujo de dióxido de carbono constante de 30 g.min-1 y un tiempo de extracción de 150 min. Se planteó un diseño experimental compuesto central para estudiar el efecto de la presión (P) y la temperatura (T) sobre el rendimiento, el perfil de ácidos grasos y esteroles. La composición en ácidos grasos y esteroles se analizó por cromatografía d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
3
7
0
5
Order By: Relevance
“…Soursop seed oil extracted by SFE contained 27.6% saturated fatty acids and 70.0% unsaturated fatty acids ( Table 2 ). Similar fatty acid profiles have also been reported in the literature, with unsaturated fatty acid percentages of 64–75% ( Dorado et al, 2016 , Pinto et al, 2018 ). The major compounds identified in terms of the relative area percentage and/or relevance in the extracts were the unsaturated fatty acids, oleic acid (ω9), 10,13-octadecadienoic acid (PUFA), linoleic acid (ω6), palmitoleic acid (ω7), and elaidic acid (a trans geometric isomer of oleic acid), as well as saturated fatty acids, palmitic acid, and stearic acid.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Soursop seed oil extracted by SFE contained 27.6% saturated fatty acids and 70.0% unsaturated fatty acids ( Table 2 ). Similar fatty acid profiles have also been reported in the literature, with unsaturated fatty acid percentages of 64–75% ( Dorado et al, 2016 , Pinto et al, 2018 ). The major compounds identified in terms of the relative area percentage and/or relevance in the extracts were the unsaturated fatty acids, oleic acid (ω9), 10,13-octadecadienoic acid (PUFA), linoleic acid (ω6), palmitoleic acid (ω7), and elaidic acid (a trans geometric isomer of oleic acid), as well as saturated fatty acids, palmitic acid, and stearic acid.…”
Section: Resultssupporting
confidence: 88%
“…Corroborating these results, Santos et al, 2018 , Dorado et al, 2016 reported the extraction yields of 6.9% and 12.9%, respectively, for soursop seeds using SFE under different conditions (20 MPa, 40 °C, 0.12 kg CO 2 ∙h −1 , and 145 min and 38.1 MPa, 49.8 °C, 1.8Kg CO 2 ∙h −1 and 150 min, respectively).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Tamarillo seed oil obtained with SC‐CO2 presented a saturated fatty acid content of 11.80, 16.18% monounsaturated fatty acid content, and 72.05% polyunsaturated fatty acid content, which is similar to those reported in other studies . The high polyunsaturated content is due principally to its linoleic content, as in passion fruit seed oil (72.7%) and grape seed oil (70–78%) .…”
Section: Resultssupporting
confidence: 86%
“…The extraction yield and selectivity depend on different factors such as the technique and the extraction parameters employed and the type of solvent or the geographical area where the fruits are grown (Pantoja-Chamorro et al 2017a). SFE employs green solvents such as carbon dioxide and it commonly allows obtaining higher efficiency, selectivity, and recoveries working under mild conditions, thus favoring the extraction of bioactive and thermolabile compounds (Dorado et al 2016;Herrero et al 2006;Herrero et al 2013).…”
Section: Introductionmentioning
confidence: 99%